The Relationship between Comorbidities and Mortality among Covid-19 Patients at Raden Mattaher General Hospital in Jambi - Fesi Putri Alwi; Makrup Efendy; Mara Imam Taufiq Siregar; Dicky Wahyudi; Wahyu Indah Dewi Aurora; Fitriyanti Fitriyanti (Jurnal Indonesia Sosial Sains, 2026)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Patients with comorbidities have a higher risk of mortality compared to patients without comorbidities. Objective: This study aims to analyze the relationship between comorbidities and mortality in COVID-19 patients at Raden Mattaher General Hospital in Jambi. Methods: This study is an observational analytical study with a retrospective approach using a cross-sectional design. The minimum sample size was 133 patients with comorbidities and 133 patients without comorbidities. The study utilized secondary data in the form of medical records, and the analysis employed the Chi-Square test. Results: The study sample consisted of 294 patients. Regarding sample characteristics, the largest age group was 56–64 years (27.6%), and the sample was predominantly male (54.4%). The most common comorbidities were diabetes mellitus (21.1%), hypertension (10.2%), chronic kidney disease (9.2%), hypertensive heart disease (5.4%), acute kidney injury (2.4%), and tuberculosis (1.7%). The proportion of patients with a deceased status was (15.3%) Bivariate analysis results indicated an association between comorbidities and mortality among COVID-19 patients at Raden Mattaher General Hospital in Jambi, with a p-value of 0.006 (p < 0.05). Conclusion: There is an association between comorbidities and mortality in COVID-19 patients at Raden Mattaher General Hospital in Jambi.